The Development of Bali's Cocoa Industry through the Hexagon Model for Local Economic Development (LED): Sorga Chocolate Factory - Zia'ulhaq As Shidqi; Muhammad Abdul Azis; Ni Nyoman Clara Listya Dewi; Walda Okvi Juliana Ningsih (Journal of World Trade Studies, 2021)
Local Economic Development (LED) is the foundation for maintaining the national economic cycle and supporting local financial independence. In addition to its tourism sector, Bali has potential in the cocoa industry. In 2009, Bali had 12,850 hectares of cocoa land. Balinese cocoa is also famous for its taste and fermentation quality. Unfortunately, the cocoa industry still has several challenges, such as cocoa farmers being comfortable with the value chain formed by the world's largest cocoa companies, Indonesian cocoa's renowned mixed and low-quality cocoa; access to buyers; different prices between farmers, wholesaler, and lead firms; productivity consistency and quality in the upstream sector; and climate change. This research will examine the cocoa industry in Bali using the Hexagon Model for LED and also analyze the upstream-downstream process of the Balinese cocoa industry. The objective of this article is to examine how the Hexagon model for LED in the Balinese cocoa industry can further activate local economic activities and form a resilient and sustainable local economy. The local government has established regulations for the protection of cocoa farmers in collaboration with Kalimajari and Udayana University, however, optimization in implementing the regulations still need to be done, especially in the government sector